Prognostic capacity of D-dimer in predicting mortality in patients diagnosed with COVID-19: Capacidad pronóstica del dimero D en la predicción de mortalidad en pacientes con el diagnóstico de COVID-19 - Alburqueque-Melgarejo, Joseph (2024)
Abstract Introduction: SARS-CoV-2 infection can produce a hypercoagulable state and increase the risk of developing thrombotic events. Several observational studies have reported an association between D-dimer levels on admission and mortality from COVID-19. Objective: The objective of the present study was to determine the prognostic capacity of D-dimer in predicting mortality from COVID-19 in patients hospitalized in the Intensive Care Unit. Methods: An observational, analytical and retrospective cohort design was used. A sample size of 324 hospitalized patients was calculated, who were followed during the period January to July 2021 to evaluate the outcome of disease. For statistical analysis, the SPSS version 26 statistical package was used. Results: A cut-off point of 1.40 µg/mL was calculated for D-dimer values ​​with a sensitivity of 80.9%, a specificity of 86.4% and area under the curve (AUC) of 0.916 (CI 95%: 0.884 – 0.947; p =0.016) to predict mortality from COVID-19. Likewise, it was found that patients with D-dimer values ​​greater than or equal to 1.40 µg/mL had an increased risk of mortality in patients with COVID-19 (HRa = 6.545; 95% CI: 3.867 – 11.077; p<0.001), independent of the variables of age, diabetes mellitus, arterial hypertension, ischemic heart disease, cerebrovascular disease, atrial fibrillation, chronic obstructive pulmonary disease, asthma, cancer and thrombocytopenia. Conclusions: The present study showed that D-dimer levels on admission represent a reliable biomarker in the evaluation of the prognosis of patients with COVID-19.